THE EFFECT OF MOTIVATIONAL BELIEFS AND LIFE CONTEXT ON MOTHER INVOLVEMENT IN EARLY CHILDHOOD EDUCATION - Nurjanah, Siti; Neti Hernawati (Journal of Child, Family, and Consumer Studies, 2024)
One of the crucial role of families in children's education is parents' involvement in early childhood education. However, several research results indicate that the involvement of parents in children's education is still low. This study aims to analyze the influence of motivational beliefs and life context on parental involvement in early childhood education. This study involved 86 respondents consisting of 43 respondents from Babakan Village and 43 respondents from Dramaga Village that selected purposively with the criteria of having children aged 3-5 years and being students in PAUD in both villages. Data were collected using interview techniques with questionnaire tools. The data analysis used was correlation test and regression tests. The results showed that the mother involvement, motivational beliefs, and life context scores of the mother were low. Mother characteristics that were significantly positively related to the motivational beliefs and life context variables were mother occupation and per capita income. The result indicates that motivational beliefs and life context are both associated with mother involvement. Children's age, mother's age, mother education, per capita income, and family size have no significant effect on mother involvement. Motivational beliefs and life context have a positive effect on mother involvement.